Existence of Polynomial Combinatorics Graph Solution - Mardiningsih; Suwilo, Saib; Hasbiyati, Ihda (Talenta Publisher, 2020)
The Polynomial Combinatorics comes from optimization problem combinatorial in form the nonlinear and integer programming. This paper present a condition such that the polynomial combinatorics has solution. Existence of optimum value will be found by restriction of decision variable and properties of feasible solution set or polyhedra.